Development of Fast Alcohol Screening Test Implementation and Electronic Nursing Interventions for Adolescents with Alcohol Abuse: A Literature Review - Triaswati, Rusmai; Hariyati, Rr. Tutik Sri; Daulima, Novy Helena Catharina (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This literature review aims to theoretically analyze the rationale for developing this electronic application to cover all aspects of adolescent mental health life and as a promotive and preventive tool for adolescents with alcohol abusers. Methods: The literature review method was carried out on ten articles which were obtained from five databases namely PUBMED, Google Scholar, ClinicalKey Nursing, ProQuest, Science Direct. The keywords for article search were "FAST (Fast alcohol screening test)", "electronic-based nursing care", "alcohol abuse", "adolescent". The criteria for articles considered included articles available in English and Indonesian and published between 2017 and 2023. Results: This review shows that the use of FAST and electronic-based nursing care can improve the quality of nursing care. Conclusion: The utilization of technology in the screening test process and electronic based nursing care in nursing care is one of the alternative problem solving and especially can improve the quality of nursing care.